Economic development - Todaro, Michael P.; Smith, Stephen C. (Boston : Pearson Addison Wesley, 2006)
Introduces economic models within the context of countries and issues, so that students learn to analyze and engage in ongoing policy debates. It helps students to evaluate issues using the best available cross-sectional data, economic theory, and institutional and structural perspectives. Keeping pace with current data and events, the Ninth Edition includes the latest research in development as well as extensive country-specific examples of topics such as transition economics and urban policy.
Includes bibliographical references and index.
oif 30/04/15
Loan
Keywords: Economic development; Developing countries